2021
DOI: 10.1039/d0cs00443j
|View full text |Cite
|
Sign up to set email alerts
|

The rise of metal–organic polyhedra

Abstract: Metal–organic polyhedra (MOPs) are comprehensively summarized and classified based on topology, providing new directions for MOP design and forthcoming applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
147
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(161 citation statements)
references
References 189 publications
1
147
0
Order By: Relevance
“…This ligand displays a bent angle of α = 149°. [27] Heating a mixture of L1 (1 equiv), L5 (1 equiv), and [Pd(CH 3 CN) 4 ](BF 4 ) 2 (1 equiv) in CD 3 CN to 70°C for 7 days gave again a defined assembly, as evidenced by 1 H and DOSY NMR spectroscopy (Figures S23-S26). However, the HRMS data suggested that a hexanuclear instead of a tetranuclear complex had formed (Figure S27).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…This ligand displays a bent angle of α = 149°. [27] Heating a mixture of L1 (1 equiv), L5 (1 equiv), and [Pd(CH 3 CN) 4 ](BF 4 ) 2 (1 equiv) in CD 3 CN to 70°C for 7 days gave again a defined assembly, as evidenced by 1 H and DOSY NMR spectroscopy (Figures S23-S26). However, the HRMS data suggested that a hexanuclear instead of a tetranuclear complex had formed (Figure S27).…”
Section: Resultsmentioning
confidence: 92%
“…All these parameters can influence the self-assembly reaction. [1][2][3][4][5][6][7][8][9][10][11] Evidently, the reaction partner needs to be taken into account, and the ligand should be a good match for the corresponding metal ion (or complex).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attractive properties of MOFs have largely been underpinned by important design principles surrounding their net topology ( Robson 2000 ), isoreticular chemistry ( Furukawa et al, 2013 ), and post-synthetic chemistry ( Mandal et al, 2021 ). Over the past decade, it has been demonstrated that discrete molecular compounds, such as porous organic cages and metal-organic cages (MOCs), possess many of the attractive properties of MOFs ( Hasell and Cooper, 2016 ; Lee et al, 2021 ; Pullen and Clever, 2018 ). Unlike MOFs, MOCs are inherently soluble, and this characteristic opens up avenues for solution processing and hybridization with organic polymers ( Pastore and Cook, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The structural directing role of the bridging ligand as a non-metallic inverse coordination center (centroligand) is the cornerstone of the ICC viewpoint. Moreover, it is ultimately responsible for the magnetic properties of a unique class of IPCs and ICPs with paramagnetic 3d–5d metal ions that behave as molecular nanomagnets and molecule-based magnets [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. They include discrete metal-fluoride rings [ 25 , 26 , 27 , 28 ], metal-oxo clusters [ 29 , 30 , 31 ], and metal-cyanide polyhedra [ 32 ], as well as a variety of chains, layers, and different networks with cyanide [ 33 , 34 ] and polycyanocarbon anion radicals [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%